The Variety of Educational Communicative Situations of Virtual Urbanism as an Effective Tool for the Formation of Students’ Communicative Competence in Learning Foreign Languages in Russia, Kazakhstan and China - Aknur S. Baimakhan; Gulbarshyn K. Belgibayeva; Irina S. Karabulatova; Jiadong Hu; Jinna Zou (Виртуальная коммуникация и социальные сети, 2024)
The formation of foreign languages communicative competence in modern electronic and digital society is directly conditioned by the achievements of computer psycholinguistics, neurolinguistics, starting from digital neuropedagogy using the natural landscape to construct a virtual environment with a change in the speech and behavioral standard in urbanism and the priority of digital reality. The purpose of the study is to define and substantiate the methodology of digital educational resources, which gradually forms communicative competencies by immersing students in the virtual environment of urban society.The hypothesis is based on students' understanding of the process of learning foreign languages with an emphasis on the specifics of neurocognitive connections in the formation of communicative competencies using didactic computer-mediated digital technologies of various electronic educational resources by comparing real and virtual urban space. The research material is a variety of educational communicative situations of virtual urbanism. The object of this research is the process of learning a foreign language, including analog situations of the real city environment and simulation modeling of a virtual urban space. The study clarifies the concepts of communicative competence, virtual urbanism, digital technologies, indicating the parameters of the main classifications.